NOP Receptor Agonist Ro 64-6198 Decreases Escalation of Cocaine Self-Administration in Rats Genetically Selected for Alcohol Preference - Li, Hongwu; Scuppa, Giulia; Shen, Qianwei; Masi, Alessio; Nasuti, Cinzia; Cannella, Nazzareno; Ciccocioppo, Roberto (Frontiers in Psychiatry, 2019)
Cocaine dependence is a psychiatric condition for which effective medications are still lacking. Published data indicate that an increase in nociceptin/orphanin FQ (N/OFQ) transmission by NOP receptor activation attenuates cocaine-induced place conditioning and the locomotor sensitization effects of cocaine. This suggests that the activation of the N/OFQ receptor (NOP) may attenuate the motivation for psychostimulants. To further explore this possibility, we investigated the effect of the potent and selective NOP receptor agonist Ro 64-6198 on cocaine intake under 1 h short access (ShA) and 6 h long access (LgA) operant self-administration conditions in rats. We used Marchigian Sardinian alcohol-preferring (msP) rats and Wistar control rats. msP rats were used because we recently found that this rat line, originally selected for excessive alcohol drinking and preference, exhibits a greater propensity to escalate cocaine self-administration following LgA training. msP rats are also characterized by innate overexpression of the N/OFQ-NOP system compared with Wistar rats. Wistar and msP rats both exhibited an increase in cocaine self-administration under LgA conditions, with a higher trend toward escalation in msP rats. In Wistar rats, the intraperitoneal administration of Ro 64-6198 (0. 1 and 3 mg/kg) significantly decreased ShA cocaine self-administration. In Wistar rats that underwent LgA cocaine self-administration training, Ro 64-6198 induced no significant effect either during the first hour of self-administration or after the entire 6 h session. In msP rats, Ro 64-6198 significantly reduced cocaine self-administration both under ShA conditions and in the first hour of the LgA session. At the end of the 6 h session, the effect of Ro 64-6198 was no longer observed in msP rats. The highest dose of Ro 64-6198 (3 mg/kg) did not affect saccharin self-administration in msP rats but reduced saccharin self-administration in Wistar rats. Altogether, these data suggest that NOP receptor activation attenuates cocaine self-administration, and this effect tends to be more pronounced in a rat line with innately higher NOP receptor expression and that more robustly escalates cocaine intake.